HLA antigens in glaucoma and ocular hypertension. Issue 5 (May 1979) - David, R; Maier, G; Baumgarten, I; Abrahams, C
Abstract : Forty-five white patients (32 with open-angle glaucoma and 13 with ocular hypertension) and 63 black patients (41 with open-angle glaucoma and 22 with ocular hypertension) were tissue typed for a total of 38 HLA antigens and the results compared to normal, unrelated, panels of 248 white donors and 150 black volunteers, respectively. No statistically significant differences with regard to the frequencies of 38 HLA antigens were detected among the various groups.